The Influence of Financial Literacy and Financial Technology on Student Financial Behavior in Yogyakarta - Mela Rizka Nuringtyas; Kartini Kartini (International Journal of Social Service and Research, 2023)
This study aims to test the influence of financial literacy and financial technology on financial behavior in students in Yogyakarta. This study uses a purposive sampling method that can help researchers in determining research samples. This study used a sample of 300 respondents. The methods carried out in this study are descriptive analysis methods and multiple linear analysis. The data used in this study are primary data obtained from the distribution of questionnaires. This research data was processed using SPSS software. The results of this study show that: (1) financial literacy has a positive effect on student financial behavior in Yogyakarta and (2) financial technology has a positive effect on student financial behavior in Yogyakarta.